Demographic profile and pattern of fatal injuries in Nairobi, Kenya, January-June 2014 - Gladwell Koku Gathecha; Wilfred Mwai Githinji; Alfred Karagu Maina (BMC, 2017)
Abstract Background Violence and Injuries are a significant global public health concern characterized by marked regional variation in incidence. Approximately five million people die from injuries each year, accounting 9% of all deaths worldwide. In Kenya, injuries are increasingly becoming a cause of hospital admissions and mortality where they account for 10% of all the deaths. The objective of this study was to determine the magnitude, demographic profile and pattern of fatal injuries in Nairobi. Methods Retrospective review of death certificates from the Department of Civil Registration was done for deaths caused by injuries that occurred in Nairobi during the period, January to June 2014. Data was collected using a standardized form. Data entry, cleaning and analysis was done using Epi info version 7.0. Results A total of 11,443 records were reviewed. From this data, deaths resulting from injuries were 1,208 accounting for 10.6% of all recorded deaths. Majority of the deaths resulting from injuries occurred in persons aged 25 to 44 years (48.1%). Males accounted for 85% of all the injuries. The leading cause of injury was assault by blunt force at 30.5%, followed by road traffic injuries at 25.9% and fire arm injuries at 15%. Pre-hospital deaths accounted for 51.4% of all the deaths. Nineteen percent of the deaths resulting from injuries had autopsies performed on them. Conclusion Our study found that injuries are an important cause of fatality in Nairobi, accounting for one in ten deaths. There is need for multisectoral collaboration as some of the preventive measures that target the most prevalent injuries such as assault and road traffic injuries lie outside the health sector. There exists information gaps on the death certificates hence there is need to adequately capacity build both clinicians and death certifiers. There is also a need to revise the death certificates and to improve the pre-hospital care system for the injured persons.